2009
DOI: 10.17221/1744-cjas
|View full text |Cite
|
Sign up to set email alerts
|

Contents of macro- and microelements in blood serum and breast muscle of broiler chickens subjected to different variants of pre-slaughter handling

Abstract: This experiment was aimed at determining contents of Ca, Mg, Na, K, P, and Fe in blood serum and breast muscles of broiler chickens COBB 500 subjected to different variants of pre-slaughter handling in the summer period: no transport (N–T); transport to a distance of 100 km (T–100) and 200 km (T–200). The complete pre-slaughter handling consisted of the following stages: catching the birds, weighing, loading to containers, transport and waiting for slaughter, unloading and weighing after the transport. In the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 9 publications
2
10
0
3
Order By: Relevance
“…Finally, deficiencies of minerals deteriorate the quality of poultry meat. A study by Wójcik et al (2009) on the impact of transport duration on the level of minerals in tissues of chickens has demonstrated that it decreases during long-time exposure to stress stimuli (transportation of long distances) when the body is incapable of covering for the deficiencies. Results of our experiment indicate that the introduction of stress factors in the form of simultaneous crowding and changes in temperature and lighting conditions had no significant effect on concentrations of the analysed elements in tissues of turkey hens (Tables 1 and 2).…”
Section: Resultsmentioning
confidence: 99%
“…Finally, deficiencies of minerals deteriorate the quality of poultry meat. A study by Wójcik et al (2009) on the impact of transport duration on the level of minerals in tissues of chickens has demonstrated that it decreases during long-time exposure to stress stimuli (transportation of long distances) when the body is incapable of covering for the deficiencies. Results of our experiment indicate that the introduction of stress factors in the form of simultaneous crowding and changes in temperature and lighting conditions had no significant effect on concentrations of the analysed elements in tissues of turkey hens (Tables 1 and 2).…”
Section: Resultsmentioning
confidence: 99%
“…The possible reason might be due to the variation of feed intake and therefore, it is suggested that the male and female should distinctly be segregated. On the other hand, the importance of P in various activities have already been suggested and it was stated that P influences on the release of energy from protein, carbohydrate and fats while the body was exposed to stress bearing factors [24].…”
Section: Resultsmentioning
confidence: 99%
“…W wielu pracach przedstawiana jest problematyka dotycząca poziomu makro-i mikroelementów w mięsie drobiu, ale głównie w kontekście wpływu diety na ich zawartość [2,5,6,8,10,11,12,13,15,18]. Natomiast niewiele jest prac określających wpływ czynników stresowych na poziomu makro-i mikroelementów w mięsie drobiu [26]. Ograniczenie niekorzystnych skutków działania czynników stresowych występujących w obrocie przedubojowym drobiu, takich jak: zmiany w składzie krwi, straty masy ciała, uszkodzenia tuszek, zmiany w strukturze tkanki mięśniowej czy obniżenie jakości mięsa [20,22,25] możliwe jest m.in.…”
Section: Wprowadzenieunclassified